Analysis of Measles Vaccination Refusal on Social Media (Facebook) among Anti-Vaccine Communities in Indonesia - Meilani, Dwi; Martha, Evi; Pratomo, Hadi; Hasanah, Indah Jamiatun; Rungreangkulkij, Somporn (UI Scholars Hub, 2021)
Measles is one of the main causes of global mortality in the under-fives. The existence of groups that reject immunization caused a decrease in immunization coverage. Anti-vaccine messages are widely delivered on social media. Identification of vaccine rejection behavior can be used as the basis to formulate effective program strategies. The design of this study used rapid assessment procedures (RAP). The informants were from two anti-vaccine communities in the Facebook group. In-depth interviews and observations were done for data collection, and data analysis was performed using the Framework Method. The results found that determinants, such as knowledge, beliefs in health behavior and disease prevention, religion, culture, and government policies play a role in shaping informants’ perceptions of vaccines and disease risks. The design factors of vaccination programs and the reliability of vaccine producing sources were found to be inhibiting factors for informants to receive vaccines. Also, experience with vaccines, health workers' role, and lobbying by anti vaccine groups strengthened informants' attitude who initially doubted vaccines, causing them to reject vaccines ultimately. It is suggested to the Ministry of Health to improve vaccination campaigns through social media, conduct vaccine development study, and increase health workers' knowledge related to vaccines and make their communication techniques more effective.